Assessment of Macular Pigment Optical Density Using Fundus Reflectometry in Diabetic Patients - Varghese, Mary (Middle East Afr J Ophthalmol, 2019)
PURPOSE: Diabetic retinopathy (DR) is a major cause of visual disability and may be associated with reduction in macular pigment (MP) density and insufficient data are available. We present MP optical density (MPOD) measured by fundus reflectometry in eyes with and without early and moderate DR. SUBJECTS AND METHODS: This was a cross-sectional study conducted in the year 2014–2015. Participants were divided into three groups: the normal individuals without diabetes constituted Group I, while diabetic patients without DR and the patients with mild-to-moderate DR constituted Group II and Group III, respectively. MPOD and maximum optical density (Max OD) were measured using a Visucam 500 fundus camera (Carl Zeiss Meditec AG, Jena, Germany). RESULTS: Fifty diabetic patients without DR, 50 with mild and moderate DR, and 50 healthy individuals underwent MPOD and Max OD measurements. The mean pigment density was the same in all the three groups (0.12). HbA1c levels were inversely correlated with MPOD (P = 0.01) and Max OD (P = 0.002). There was no relationship between MP density and age (P = 0.66), gender (P = 0.24), or duration of diabetes (P = 0.85). The duration of diabetes was compared between the two groups of diabetic patients with and without DR. CONCLUSIONS: The mean pigment density assessed by fundus reflectometry was 0.12 in each of the three groups studied. Higher HbA1c levels in diabetic patients correlated with decreased MPOD and Max OD. Better glycemic control may influence macular health in diabetic patients.